Neurodevelopmental Precursors and Consequences of Substance Use during Adolescence: Promises and Pitfalls of Longitudinal Neuroimaging Strategies - Fishbein, Diana H.; Rose, Emma J.; Darcey, Valerie L.; Belcher, Annabelle M.; VanMeter, John W. (Frontiers in Human Neuroscience, 2016)
Neurocognitive and emotional regulatory deficits in substance users are often attributed to misuse; however most studies do not include a substance-naïve baseline to justify that conclusion. The etiological literature suggests that pre-existing deficits may contribute to the onset and escalation of use that are then exacerbated by subsequent use. To address this, there is burgeoning interest in conducting prospective, longitudinal neuroimaging studies to isolate neurodevelopmental precursors and consequences of adolescent substance misuse, as reflected in recent initiatives such as the NIH-led Adolescent Brain Cognitive Development (ABCD) study and the National Consortium on Alcohol and Neurodevelopment (NCANDA). To distinguish neurodevelopmental precursors from the consequences of adolescent substance use specifically, prospective, longitudinal neuroimaging studies with substance-naïve pre-adolescents are needed. The exemplar described in this paper – i.e., the ongoing Adolescent Development Study (ADS) - used a targeted recruitment strategy to bolster the numbers of pre-adolescent individuals who were at increased risk of substance use (i.e., “high-risk”) in a sample that was relatively small for longitudinal studies of similar phenomena, but historically large for neuroimaging (i.e., N=135; 11-13 years of age). At baseline participants underwent MRI testing and a large complement of cognitive and behavioral assessments along with genetics, stress physiology and interviews. The study methods include repeating these measures at 3 time points (i.e., baseline/Wave 1, Wave 2 and Wave 3), 18 months apart. In this paper, rather than outlining specific study outcomes, we describe the breadth of the numerous complexities and challenges involved in conducting this type of prospective, longitudinal neuroimaging study and “lessons learned” for subsequent efforts are discussed. While these types of large longitudinal neuroimaging studies present a number of logistical and scientific challenges, the wealth of information obtained about the precursors and consequences of adolescent substance use provides unique insights into the neurobiological bases for adolescent substance use that will lay the groundwork for targeted interventions.